Synthesis of New Pyrazolo[1,5-a]pyrimidines by Reaction of β,γ-Unsaturated γ-Alkoxy-α-keto Esters with N-Unsubstituted 5-Aminopyrazoles - Stepaniuk, Oleksandr O.; Matviienko, Vitalii O.; Kondratov, Ivan S.; Vitruk, Igor V.; Tolmachev, Andrei O. (Synthesis, 2013)
The reaction of β,γ-unsaturated γ-alkoxy-α-keto esters with N-unsubstituted 5-aminopyrazoles was investigated. The reaction proceeds with high regioselectivity and is considered as an effective method for the preparation of new pyrazolo[1,5-a]pyrimidines bearing an ester function in the 7-position. The obtained drug-like compounds have a great potential for medicinal chemistry as they closely resemble the structure of several marketed pharmaceuticals.
Keywords: heterocycles; esters; regioselectivity; pyrazolo[1,5-a]pyrimidines; 5-aminopyrazoles